An organic-inorganic covalently linked electrochromic material and its preparation method and application
By connecting electronic polyme from the metaext polymer of iron fundamentals-MO6, the metal charge transfer of the organic structure-metal charge transfer, solving the problem of unsatisfactory color regulation effects in the existing technology, realized the electrical discoloration of color transformation Effective adjustment and good reversibility of electrocarious discoloration devices.
Patent Information
- Application Number
- CN202411443705.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-10-16
AI Technical Summary
When existing organic electrochromic materials change their electrochromic properties, the color adjustment effect is not ideal, making it difficult to achieve ideal color adjustment.
By connecting electronic polymerine-MO6 by connecting electron acid-MO6 in the metaext polymer of Iron Division, the ligand-metal charge transfer of the organic structure using the common price connection to the organic structure can be used to realize the color regulation of the electroconent discoloration.
The color of the color changing color is effectively adjusted. The obtained electrical discoloration devices have good reversibility and significant color differences, and the color regulation effect is significant.
Smart Images

Figure CN118955937B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of optoelectronic materials, and particularly relates to an organic-inorganic covalently linked electrochromic material and a preparation method and application thereof. Background Art
[0002] With the increase of world population and the acceleration of urbanization, the total energy consumption is also increasing rapidly. Global warming and energy crisis have accelerated the development of various energy-saving systems and energy-saving products. Organic polymers have high color rendering efficiency and good cycle stability. The π-π conjugation of the organic part of metal supramolecular polymers and the π-d conjugation between ligands and metal ions promote the transfer of electrons along the molecular skeleton, making them promising candidates for electrochromism. However, the modification of ligands is usually limited to organic structures. The ligands of organic molecules need to be modified with organic functional groups when changing the electrochromic properties, which leads to the problem of unsatisfactory color adjustment effect. Summary of the invention
[0003] In order to solve the above-mentioned technical problems, the present invention provides an organic-inorganic covalently linked electrochromic material and a preparation method and application thereof.
[0004] In order to achieve the above object, the technical solution adopted by the present invention is:
[0005] In one aspect, the present invention provides an organic-inorganic covalently linked electrochromic material, the structural formula of which is as follows: ;
[0006] Here, n is an integer greater than 1.
[0007] On the other hand, the present invention also provides a method for preparing an organic-inorganic covalently linked electrochromic material, the synthesis route of which is: ; The specific preparation steps are as follows:
[0008] Step 1, synthesis of compound (1):
[0009] Prepare solution A: Add Na 2 MoO 4 ·2H 2 O was dissolved in deionized water, 6N hydrochloric acid was slowly added dropwise, and solution A was prepared with vigorous stirring;
[0010] Prepare solution B: dissolve tetrabutylammonium bromide in deionized water to prepare solution B;
[0011] Pour the prepared solution B into solution A under vigorous stirring to form a white precipitate; continue stirring and filter; collect and filter the precipitate, wash it with water, ethanol, acetone and ether in sequence until the filtrate is clear, dissolve the crude product in acetonitrile, the amount of acetonitrile added is such that the crude product is completely dissolved, and store it at -20°C for more than 12 hours; collect the solid by suction, and form a white powder after drying, which is compound (1);
[0012] Step 2, synthesis of compound (2):
[0013] 2,6-Diisopropylaniline was dissolved in cyclohexane and then saturated Na 2 CO 3 aqueous solution and solid iodine, the reaction was stirred at room temperature; the crude solution was diluted with ether and washed with saturated Na 2 S 2 O 3 The aqueous solution is washed until the waste liquid is clear, and then the organic layer is dried with anhydrous sodium sulfate until the anhydrous sodium sulfate does not clump, and concentrated under vacuum to obtain a dark red oily substance, which is compound (2);
[0014] Step 3, synthesis of compound (3):
[0015] Compound (2), N,N'-dicyclohexylcarbodiimide and compound (1) are dissolved in anhydrous acetonitrile and refluxed for 24 hours under nitrogen protection, and filtered to obtain a dark red filtrate, from which the product is precipitated in the form of orange crystals; the product is collected by filtration, washed with ethanol and ether in turn until the filtrate is clear, and then recrystallized twice in acetone to obtain compound (3);
[0016] Step 4, synthesis of compound (4):
[0017] Dissolve p-ethynylbenzaldehyde, 2-acetylpyridine and sodium hydroxide in a mixed solution of anhydrous ethanol and aqueous ammonia, stir overnight and let stand, then filter to obtain a powder, which is compound (4);
[0018] Step 5, synthesis of compound (5):
[0019] Compound (3), Pd(PPh 3 ) 2 Cl 2 and CuI were dissolved in 10 mL of DMF (N,N-dimethylformamide) and stirred under nitrogen protection. Compound (4) and triethylamine were then added and stirred for 30 min. Then, dichloromethane was added to dilute the mixture. The red filtrate was filtered and washed with water and saturated brine in turn until the waste liquid was clear. The organic layer was collected and precipitated with MgSO 4 Dry to MgSO 4The reaction mixture was stirred for 2 hours until no lumps formed, and concentrated under vacuum; the concentrated solution was poured into hexane and kept standing; the precipitate was collected by filtration and dried under vacuum to obtain an orange solid, which is compound (5);
[0020] Step 6, synthesis of compound (6):
[0021] Compound (5), ferric acetate and acetic acid were refluxed under nitrogen atmosphere for 24 hours. After filtration, the solid was washed with acetic acid and ethanol in sequence until the filtrate was colorless, thereby obtaining a purple solid, which was compound (6), i.e., an organic-inorganic covalently linked electrochromic material.
[0022] Further, in step 1, the preparation solution A is specifically 20.7 mmol of Na 2 MoO 4 ·2H 2 O was dissolved in 10 mL of deionized water, 5.17 mL of 6N hydrochloric acid was slowly added dropwise, and stirred vigorously for 1-2 min to prepare solution A;
[0023] The preparation of solution B specifically comprises dissolving 10.4 mmol of tetrabutylammonium bromide in 10 mL of deionized water to obtain solution B.
[0024] Further, in step 2, the amount of 2,6-diisopropylaniline is 14.3 mmol, the amount of cyclohexane is 20 mL, and the saturated Na 2 CO 3 The amount of aqueous solution used is 4 mL, the amount of solid iodine used is 15.7 mmol, the amount of ether used is 30 mL, and the stirring time is 11 h;
[0025] In step 3, the amount of compound (2) used is 2 mmol, the amount of N,N'-dicyclohexylcarbodiimide used is 2 mmol, the amount of compound (1) used is 1 mmol, and the amount of anhydrous acetonitrile used is 16 mL;
[0026] In step 4, the amount of p-ethynylbenzaldehyde is 7.68 mmol, the amount of 2-acetylpyridine is 15.37 mmol, the amount of sodium hydroxide is 30.74 mmol; the amount of anhydrous ethanol is 50 mL, and the amount of ammonia water is 35 mL;
[0027] In step 5, the amount of compound (3) used is 0.207 mmol, Pd(PPh 3 ) 2 Cl 2 The amount of is 0.0124mmol, the amount of CuI is 0.0248mmol; the amount of compound (4) is 0.826mmol, the amount of triethylamine is 3.42mmol, the amount of dichloromethane is 20mL, and the amount of hexane is 200mL;
[0028] In step 6, the amount of compound (5) used is 0.1 mmol, the amount of iron acetate used is 0.2 mmol, and the amount of acetic acid used is 50 mL.
[0029] In a third aspect, the present invention also provides an application of an organic-inorganic covalently linked electrochromic material in the preparation of an electrochromic device.
[0030] Furthermore, the method for preparing an electrochromic device specifically comprises the following steps:
[0031] Step a, completely dissolving 0.1 g of the above-mentioned organic-inorganic covalently linked electrochromic material in N,N-dimethylformamide, wherein the amount of N,N-dimethylformamide used is such that the organic-inorganic covalently linked electrochromic material is completely dissolved to obtain a clear solution;
[0032] Step b, the clarified solution is transferred into a syringe and sprayed on a piece of FTO glass by electrostatic spraying to obtain a layer of electrochromic material film, which is the electrochromic layer;
[0033] Step c, adding acrylamide, lithium perchlorate, N,N-methylenebisacrylamide and potassium persulfate to deionized water, stirring to form a uniform clear solution, and cross-linking the clear solution at 60° C. for 2 hours to obtain a polyacrylamide-lithium perchlorate gel;
[0034] Step d, preparing a titanium dioxide slurry and ethanol into a solution with a titanium dioxide slurry mass concentration of 40%, spin coating the solution on another piece of FTO glass, and then sintering to obtain a titanium dioxide film as a charge balance layer;
[0035] Step e: sandwich the polyacrylamide-lithium perchlorate gel between two FTO glass electrochromic material films and titanium dioxide films as an ion transport layer to assemble into a "sandwich-type" electrochromic device.
[0036] Furthermore, the spraying conditions in step b are 20 kV high voltage static electricity and 1 mL / h propulsion speed, and the spraying time is 5 hours.
[0037] Furthermore, in step c, the amount of deionized water added is 10 mL, the amount of acrylamide added is 1 g, the amount of lithium perchlorate added is 1.06 g, the amount of N,N-methylenebisacrylamide added is 0.001 g, and the amount of potassium persulfate added is 0.005 g.
[0038] Furthermore, the spin coating conditions in step d are a speed of 1000 r / min and a spin coating time of 30 s.
[0039] Furthermore, the sintering condition in step d is sintering at 450° C. for 30 minutes.
[0040] Compared with the prior art, the present invention has the following beneficial effects:
[0041] The organic-inorganic covalently linked electrochromic material of the present invention connects electron-withdrawing polyacid-Mo6 in the iron-based metal supramolecular polymer, and changes the ligand-metal charge transfer of the organic structure by covalently linking the inorganic structure, thereby adjusting the color of the electrochromic. The electrochromic device obtained by applying the organic-inorganic covalently linked electrochromic material of the present invention has good reversibility, has very obvious color difference, and has good color adjustment effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 is the compound (2) in Example 2 1 HNMR nuclear magnetic resonance spectrum.
[0043] Figure 2 is the compound (3) in Example 2 1 HNMR nuclear magnetic resonance spectrum.
[0044] Figure 3 is the compound (4) in Example 2 1 HNMR nuclear magnetic resonance spectrum.
[0045] Figure 4 is the compound (5) in Example 2 1 HNMR nuclear magnetic resonance spectrum.
[0046] Figure 5 This is a photo of the solutions of compound (6) and compound (8) in Example 2.
[0047] Figure 6 It is the absorbance spectrum of compound (6) and compound (8) in Example 2.
[0048] Figure 7 This is the CIE chromaticity diagram of compound (6) and compound (8) in Example 2.
[0049] Figure 8 It is the CV graph of the electrochromic device prepared in Example 3 at different scan rates under a voltage of 0.5-1.5V.
[0050] Fig. 9 Graph showing transmittance of the electrochromic device prepared in Example 3 at different voltages.
[0051] Fig.10 This is the CIE chromaticity diagram of the color of the electrochromic device prepared in Example 3 of the present invention at different voltages. DETAILED DESCRIPTION
[0052] In order to highlight the technical advantages and excellent performance of the present invention, the following will be further described in conjunction with the accompanying drawings and specific embodiments. The following specific embodiments are only used for the present invention, and the specific implementation process can also be adjusted according to the understanding of technicians and actual conditions.
[0053] Example 1
[0054] The present invention provides an organic-inorganic covalently linked electrochromic material, the structural formula of which is as follows: ;
[0055] Wherein, n is an integer greater than 1; a unit chemical formula of an organic-inorganic covalently linked electrochromic material is: Mo6-[N-4-({4-[2,6-di(pyridin-2-yl)pyridin-4-yl]phenyl}ethynyl)-2,6-di(propan-2-yl)benzene] 2 @Fe 2+。
[0056] Example 2
[0057] A method for preparing an organic-inorganic covalently linked electrochromic material, the synthesis route of which is as follows: ;
[0058] The specific preparation steps are as follows:
[0059] Step 1, synthesis of compound (1):
[0060] Preparation of solution A: 20.7 mmol of Na 2 MoO 4 ·2H 2 O was dissolved in 10 mL of deionized water, 5.17 mL of 6N hydrochloric acid was slowly added dropwise, and stirred vigorously for 1-2 min to prepare solution A;
[0061] Prepare Solution B:
[0062] Dissolve 10.4 mmol of tetrabutylammonium bromide in 10 mL of deionized water to prepare solution B;
[0063] The prepared solution B was poured into the solution A under vigorous stirring to form a white precipitate; the stirring was continued for 10 minutes and then filtered; the amount of acetonitrile added was such that the crude product was completely dissolved, and the solution was stored at low temperature for more than 12 hours; the solid was collected by filtration and dried to form a white powder, which was compound (1);
[0064] Step 2, synthesis of compound (2):
[0065] 14.3 mmol of 2,6-diisopropylaniline was dissolved in 20 mL of cyclohexane, followed by the addition of 4 mL of saturated Na 2 CO 3 aqueous solution and 15.7 mmol of solid iodine, the reaction was stirred at room temperature for 11 h; the crude solution was diluted with 30 mL of ether and washed with saturated Na 2 S 2 O 3 The aqueous solution is washed until the waste liquid is clear, and then the organic layer is dried with anhydrous sodium sulfate until the anhydrous sodium sulfate does not agglomerate, and concentrated under vacuum to obtain a dark red oily substance, which is compound (2); 1 HNMR nuclear magnetic resonance spectrum Figure 1 As shown;
[0066] Step 3, synthesis of compound (3):
[0067] 2 mmol of compound (2), 2 mmol of N,N'-dicyclohexylcarbodiimide and 1 mmol of compound (1) were dissolved in 16 mL of anhydrous acetonitrile and refluxed for 24 h under nitrogen protection. A dark red filtrate was obtained by filtration. The product was precipitated from the filtrate in the form of orange crystals. The filtered precipitate was collected and washed with water, ethanol, acetone and ether in turn until the filtrate was clear. The crude product was dissolved in acetonitrile. The product was collected by filtration, washed with ethanol and ether in turn until the filtrate was clear, and then recrystallized twice in acetone (the amount of acetone used was such that the product was completely dissolved) to obtain compound (3). 1 HNMR nuclear magnetic resonance spectrum Figure 2 As shown;
[0068] Step 4, synthesis of compound (4):
[0069] 7.68 mmol of p-ethynylbenzaldehyde, 15.37 mmol of 2-acetylpyridine and 30.74 mmol of sodium hydroxide were dissolved in a mixed solution of 50 mL of anhydrous ethanol and 35 mL of aqueous ammonia, stirred overnight and allowed to stand, and then filtered to obtain a powder, which was compound (4); 1 HNMR nuclear magnetic resonance spectrum Figure 3 As shown;
[0070] Step 5, synthesis of compound (5):
[0071] 0.207 mmol of compound (3), 0.0124 mmol of Pd(PPh 3 ) 2 Cl 2 , 0.0248 mmol of CuI was dissolved in DMF. The amount of DMF used was such that compound (3), Pd(PPh 3 ) 2Cl 2 and CuI were completely dissolved, and stirred for 10 min under nitrogen protection, then 0.826 mmol of compound (4) and 3.42 mmol of triethylamine were added, and stirring continued for 30 min, and then 20 mL of dichloromethane was poured in for dilution; the red filtrate obtained by suction filtration was washed with water and saturated brine in turn until the waste liquid was clear; the organic layer was collected and MgSO 4 Dry to MgSO 4 The concentrated solution was poured into 200 mL of hexane and allowed to stand; the precipitate was collected by filtration and dried under vacuum to obtain an orange solid, which is compound (5); 1 HNMR nuclear magnetic resonance spectrum Figure 4 As shown;
[0072] Step 6, synthesis of compound (6):
[0073] 0.1 mmol of compound (5), 0.2 mmol of ferric acetate and 50 mL of acetic acid were refluxed under nitrogen atmosphere for 24 h. After filtration, the solid was washed with acetic acid and ethanol in sequence until the filtrate was colorless to obtain a purple solid, which was compound (6), i.e., an organic-inorganic covalently linked electrochromic material.
[0074] Example 3
[0075] The method for preparing an electrochromic device specifically comprises the following steps:
[0076] Step a, completely dissolving 0.1 g of the above-mentioned organic-inorganic covalently linked electrochromic material in N,N-dimethylformamide, wherein the amount of N,N-dimethylformamide used is such that the organic-inorganic covalently linked electrochromic material is completely dissolved to obtain a clear solution;
[0077] Step b, the clarified solution is transferred into a syringe and sprayed on a piece of FTO glass to obtain an electrochromic material film, which is an electrochromic layer;
[0078] Step c, adding 1 g acrylamide, 1.06 g lithium perchlorate, 0.001 g N,N-methylenebisacrylamide and 0.005 g potassium persulfate to 10 mL deionized water, stirring to form a uniform clear solution, cross-linking the clear solution at 60° C. for 2 hours to obtain a polyacrylamide-lithium perchlorate gel;
[0079] Step d, preparing a titanium dioxide slurry and ethanol into a solution with a titanium dioxide slurry mass concentration of 40%, spin coating the solution on another piece of FTO glass, and then sintering at 450° C. for 30 minutes to obtain a titanium dioxide film as a charge balance layer;
[0080] Step e: sandwich the polyacrylamide-lithium perchlorate gel between two FTO glass electrochromic material films and titanium dioxide films as an ion transport layer to assemble into a "sandwich-type" electrochromic device.
[0081] In this embodiment, the size of the FTO glass is 2 cm×3 cm.
[0082] The spraying conditions in step b are 20 kV high voltage static electricity and 1 mL / h propulsion speed, and the spraying time is 5 hours.
[0083] The spin coating conditions in step d are a speed of 1000 r / min and a spin coating time of 30 s.
[0084] Comparative Example
[0085] As a control group, a compound without polyacid as a covalent bond was used for comparison, and the structural formula is as follows: ;
[0086] The chemical formula is: 4-({4-[2,6-di(pyridin-2-yl)pyridin-4-yl]phenyl}ethynyl)-2,6-di(propan-2-yl)aniline@Fe 2+ ; The synthetic route is shown below: ;
[0087] Synthesis of compound (7): 0.2 mmol of compound (2), 0.0062 mmol of Pd(PPh 3 ) 2 Cl 2 , 0.0124 mmol of CuI was dissolved in 10 mL of DMF and stirred for 10 min under nitrogen protection. Then 0.2 mmol of compound (4) and 1.7 mmol of triethylamine were added and stirred for 30 min. Then 20 mL of dichloromethane was poured in to dilute. The red filtrate obtained by suction filtration was washed with water and saturated brine in turn until the waste liquid was clear. The organic layer was collected and precipitated with MgSO 4 Dry to MgSO 4 The product was free of lumps and concentrated under vacuum to remove dichloromethane to obtain a concentrated solution; the concentrated solution was poured into 200 mL of hexane and allowed to stand; the precipitate was collected by filtration and dried under vacuum to obtain an orange solid, namely compound (7);
[0088] Synthesis of compound (8): 0.2 mmol of compound (7), 0.2 mmol of ferric acetate and 50 mL of acetic acid were refluxed under nitrogen atmosphere for 24 h. After filtration, the solid was washed with acetic acid and ethanol in sequence until the filtrate was colorless to obtain a purple solid, namely compound (8).
[0089] Experimental results test:
[0090] 1. Absorbance test of compound (6) prepared in Example 2 of the present invention and compound (8) of the comparative example: The actual pictures of the solutions of compound (6) and compound (8) are as follows: Figure 5 shown.
[0091] Compound (6) and compound (8) were dissolved in DMF and the absorbance was measured in a UV-visible spectrophotometer. Figure 6 As shown in the figure, after covalently linking Mo6, the peak at 583nm blue-shifted to 578nm, and a broad peak appeared at 360-470nm. It can be seen that due to the electron-withdrawing effect of the inorganic clusters in compound (6), the ligand-metal charge transfer was changed, and finally the color development appeared as follows: Figure 7 The difference shown (1→2) indicates that the polyacid Mo6 plays a role in charge transfer in the structure, thereby changing the color.
[0092] 2. Performance test of the electrochromic device prepared by the present invention:
[0093] 1. Electrochemical testing
[0094] like Figure 8 As shown, when the electrochromic device prepared in Example 3 of the present invention is subjected to a voltage of 0.5-1.5 V and different scan rates of 10-150 mV / s, the redox peak of the electrochromic device hardly shifts, indicating that the system is hardly affected by the scan rate and has good reversibility.
[0095] 2. Electrochromic performance test
[0096] like Fig. 9 As shown in FIG. 1 , in the visible spectrum test under different voltages, the electrochromic device prepared in Example 3 has very obvious color differences, and the maximum light modulation range is 40%. Since the color change between different colors cannot be fully reflected by the maximum light modulation range, it can be Fig.10 Quantified color changes can be seen in
[0097] The above contents are only preferred embodiments of the present invention. For ordinary technicians in this field, many changes can be made in the specific implementation methods and application scopes based on the ideas of the present invention. As long as these changes do not deviate from the concept of the present invention, they all belong to the protection scope of the present invention.
Claims
1. An organic-inorganic covalently linked electrochromic material, characterized in that: The structural formula is as follows: ; Here, n is an integer greater than 1.
2. The method for preparing an organic-inorganic covalently linked electrochromic material according to claim 1, characterized in that: Its synthetic route is: ; The specific preparation steps are as follows: Step 1, synthesis of compound (1): Preparation of solution A: Dissolve Na2MoO4·2H2O in deionized water, slowly add 6N hydrochloric acid dropwise, and stir vigorously to prepare solution A; Prepare solution B: dissolve tetrabutylammonium bromide in deionized water to prepare solution B; The prepared solution B was poured into solution A under vigorous stirring to form a white precipitate; Continue stirring and filter; collect the filtered precipitate, wash it with water, ethanol, acetone and ether in sequence until the filtrate is clear, dissolve the crude product in acetonitrile, the amount of acetonitrile added is such that the crude product is completely dissolved, and store it at -20°C for more than 12 hours; collect the solid by filtration, and form a white powder after drying, which is compound (1); Step 2, synthesis of compound (2): Dissolve 2,6-diisopropylaniline in cyclohexane, then add saturated aqueous Na2CO3 solution and solid iodine, and stir the reactants at room temperature; dilute the crude solution with ether, and wash with saturated aqueous Na2S2O3 solution until the waste liquid is clear, then dry the organic layer with anhydrous sodium sulfate until the anhydrous sodium sulfate does not agglomerate, and concentrate under vacuum to obtain a dark red oil, which is compound (2); Step 3, synthesis of compound (3): Compound (2), N,N'-dicyclohexylcarbodiimide and compound (1) are dissolved in anhydrous acetonitrile and refluxed for 24 hours under nitrogen protection, and filtered to obtain a dark red filtrate, from which the product is precipitated in the form of orange crystals; the product is collected by filtration, washed with ethanol and ether in turn until the filtrate is clear, and then recrystallized twice in acetone to obtain compound (3); Step 4, synthesis of compound (4): Dissolve p-ethynylbenzaldehyde, 2-acetylpyridine and sodium hydroxide in a mixed solution of anhydrous ethanol and aqueous ammonia, stir overnight and allow to stand, then filter to obtain a powder, which is compound (4); Step 5, synthesis of compound (5): Compound (3), Pd(PPh3)2Cl2 and CuI are dissolved in DMF and stirred under nitrogen protection, then compound (4) and triethylamine are added, and stirring is continued for 30 minutes, and then dichloromethane is poured into the mixture for dilution; the red filtrate obtained by suction filtration is washed with water and saturated brine in turn until the waste liquid is clear; the organic layer is collected, dried with MgSO4 until the MgSO4 does not agglomerate, and concentrated under vacuum; the concentrated solution is poured into hexane and kept standing; the precipitate is collected by filtration and dried under vacuum to obtain an orange solid, which is compound (5); Step 6, synthesis of compound (6): Compound (5), ferric acetate and acetic acid were refluxed under nitrogen atmosphere for 24 hours. After filtration, the solid was washed with acetic acid and ethanol in sequence until the filtrate was colorless, thereby obtaining a purple solid, which was compound (6), i.e., an organic-inorganic covalently linked electrochromic material.
3. The method for preparing an organic-inorganic covalently linked electrochromic material according to claim 2, characterized in that: In step 1, the preparation of solution A is specifically to dissolve 20.7 mmol of Na2MoO4·2H2O in 10 mL of deionized water, slowly dropwise add 5.17 mL of 6N hydrochloric acid, and vigorously stir for 1-2 minutes to obtain solution A; The preparation of solution B specifically comprises dissolving 10.4 mmol of tetrabutylammonium bromide in 10 mL of deionized water to obtain solution B.
4. The method for preparing an organic-inorganic covalently linked electrochromic material according to claim 2, characterized in that: In step 2, the amount of 2,6-diisopropylaniline is 14.3 mmol, the amount of cyclohexane is 20 mL, the amount of saturated Na2CO3 aqueous solution is 4 mL, the amount of solid iodine is 15.7 mmol, the amount of ether is 30 mL, and the stirring time is 11 h; In step 3, the amount of compound (2) used is 2 mmol, the amount of N,N'-dicyclohexylcarbodiimide used is 2 mmol, the amount of compound (1) used is 1 mmol, and the amount of anhydrous acetonitrile used is 16 mL; In step 4, the amount of p-ethynylbenzaldehyde is 7.68 mmol, the amount of 2-acetylpyridine is 15.37 mmol, the amount of sodium hydroxide is 30.74 mmol; the amount of anhydrous ethanol is 50 mL, and the amount of ammonia water is 35 mL; In step 5, the amount of compound (3) used is 0.207 mmol, the amount of Pd(PPh3)2Cl2 used is 0.0124 mmol, the amount of CuI used is 0.0248 mmol, and the amount of DMF used is 10 mL; the amount of compound (4) used is 0.826 mmol, the amount of triethylamine used is 3.42 mmol, the amount of dichloromethane used is 20 mL, and the amount of hexane used is 200 mL; In step 6, the amount of compound (5) used is 0.1 mmol, the amount of iron acetate used is 0.2 mmol, and the amount of acetic acid used is 50 mL.
5. Use of the organic-inorganic covalently linked electrochromic material according to claim 1 in the preparation of an electrochromic device.
6. Use of the organic-inorganic covalently linked electrochromic material according to claim 5 in the preparation of an electrochromic device, characterized in that: The method for preparing an electrochromic device specifically comprises the following steps: Step a, completely dissolving 0.1 g of the above-mentioned organic-inorganic covalently linked electrochromic material in N,N-dimethylformamide, wherein the amount of N,N-dimethylformamide used is such that the organic-inorganic covalently linked electrochromic material is completely dissolved to obtain a clear solution; Step b, the clarified solution is transferred into a syringe and sprayed on a piece of FTO glass by electrostatic spraying to obtain a layer of electrochromic material film, which is the electrochromic layer; Step c, adding acrylamide, lithium perchlorate, N,N-methylenebisacrylamide and potassium persulfate to deionized water, stirring to form a uniform clear solution, and cross-linking the clear solution at 60° C. for 2 hours to obtain a polyacrylamide-lithium perchlorate gel; Step d, preparing a titanium dioxide slurry and ethanol into a solution with a titanium dioxide slurry mass concentration of 40%, spin coating the solution on another piece of FTO glass, and then sintering to obtain a titanium dioxide film as a charge balance layer; Step e: sandwich the polyacrylamide-lithium perchlorate gel between two FTO glass electrochromic material films and titanium dioxide films as an ion transport layer to assemble into a "sandwich-type" electrochromic device.
7. Use of the organic-inorganic covalently linked electrochromic material according to claim 6 in the preparation of an electrochromic device, characterized in that: The spraying conditions in step b are 20 kV high voltage static electricity and 1 mL / h propulsion speed, and the spraying time is 5 hours.
8. Use of the organic-inorganic covalently linked electrochromic material according to claim 6 in the preparation of an electrochromic device, characterized in that: In the step c, the amount of deionized water added is 10 mL, the amount of acrylamide added is 1 g, the amount of lithium perchlorate added is 1.06 g, the amount of N,N-methylenebisacrylamide added is 0.001 g, and the amount of potassium persulfate added is 0.005 g.
9. Use of the organic-inorganic covalently linked electrochromic material according to claim 6 in the preparation of an electrochromic device, characterized in that: The spin coating conditions in step d are a speed of 1000 r / min and a spin coating time of 30 s.
10. Use of the organic-inorganic covalently linked electrochromic material according to claim 6 in preparing an electrochromic device, characterized in that: The sintering condition in the step d is sintering at 450° C. for 30 minutes.
Citation Information
Patent Citations
Polysiloxane with electrochromic property and preparation method thereof
CN106633074A
Four-membered ring pyridine multi-color electrochromic material based on different substituent groups
CN106831545A